Poverty Alleviation and Natural Resource Restoration through Community Participation : a Case Study in North-western Rajasthan - Bala, N.; Kumar, Pramod; Singh, G.; Limba, N. K. (Indian Forester, 2007)
A study was conducted on the work carried out to reclaim waterlogged area near Rawatsar of Hanumangarh District in Rajasthan, India. It was amply demonstrated that a government initiative supported by active community participation could reverse poverty linked resource degradation. The area that was under the influence of water logging and salinity since the introduction of Indira Gandhi Nahar Pariyojna (IGNP) and Ghaggar flood diversion channel stands reclaimed to a great extent after the project interventions. Surface drainage was provided to drain out stagnant water. It was supplemented by plantation of trees to biodrain water and to decrease water table further. Farmers who once fled from the area in search of living were once again seen busy with agricultural activities. Crops like cotton, wheat, and mustard etc. are now grown in the field, which was submerged under saline water a few years back. The project interventions have been proved to be a boon for that area.